Analisis Respon Guru terhadap Pengembangan Modul Praktikum Bioteknologi Berbasis Kearifan Lokal Terintegrasi Al – Qur’an - Putri, Zulgusma Aulia; Arsih, Fitri (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
This study aims to analyze and explore teachers' responses to the development of a local wisdom-based biotechnology practicum module integrated with Qur'anic values. This module is designed to improve students' understanding of biotechnology concepts through an approach that is relevant to cultural and religious contexts. The research method used was qualitative by collecting data through questionnaires and interviews. The research participants were biology teachers from various high schools. The results showed that most of the teachers gave positive responses to the developed practicum module. Teachers appreciated the integration of local wisdom with Qur'anic values, which was considered to enrich teaching materials and make learning more interesting and meaningful for students. The module is considered capable of providing a more contextual and relevant learning experience for students, as well as encouraging the strengthening of religious values in science education. Recommendations for future research include the development of teacher training and long-term evaluation of the impact of using this module on student learning outcomes